Publict Actions Toward The Saltwater Crocodile Conflict (Crocodylus porosus) With The Human In Kilangan Village Aceh Singkil District - Raudhatin Raudhatin; Abdullah Abdullah; Hafnati Rahmatan; Safrida Safrida; Devi Syafrianti (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
This study aims to determine the differences in the actions of people who have been exposed to conflicts with communities that have never been exposed to the conflict between the Crocodile and Crocodile shaft with humans. The study was conducted in August 2019. This type of research is a descriptive study with a quantitative approach. Data collection by questionnaire and interview. Data analysis with Chi-squared. Respondents in this study are people who have been exposed to conflicts and who have never been exposed to estuarine crocodile conflicts with humans. The results of this study indicate that there are differences in community actions that have experienced conflicts with those who have never experienced estuarine crocodile conflicts with humans and there are no differences in community actions that have been affected by human-crocodile conflicts in Aceh Singkil Regency in terms of education, sex and ethnicity. The conclusions are (1) There are differences in the actions of the people who have been affected by conflict with those who have never been affected by a crocodile-human conflict in Aceh Singkil District (2) There is no difference in the actions of the people who have been affected by a human-crocodile conflict in Aceh Singkil Regency based on the type of education , gender and ethnicity.Keywords: Action, Conflict, Estuary Crocodile Penelitian ini bertujuan untuk mengetahuii perbedaan tindakan masyarakat yang pernah terkena konflik dengan masyarakat yang tidak pernah terkena konflik Buaya Muara (Crocodylus porosus) dengan Manusia. Penelitian dilakukan di bulan Agustus 2019. Jenis penelitian ini adalah penelitian deskriptif dengan pendekatan kuantitatif. Pengumpulan data dengan angket dan wawancara. Analisis data dengan Chi-kuadrat. Responden dalam penelitian ini adalah masyarakat yang pernah terkena konflik dan yang tidak pernah terkena konflik buaya muara dengan manusia. Hasil penelitian ini menunjukkan bahwa terdapat perbedaan tindakan masyarakat yang pernah mengalami konflik dengan yang tidak pernah mengalami konflik buaya muara dengan manusia dan Tidak terdapat perbedaan tindakan masyarakat yang pernah terkena konflik buaya-manusia di Kabupaten Aceh Singkil ditinjau berdasarkan jenis pendidikan, jenis kelamin dan suku. Kesimpulannya adalah (1) Terdapat perbedaan tindakan masyarakat yang pernah terkena konflik dengan masyarakat yang tidak pernah terkena konflik buaya-manusia di Kabupaten Aceh Singkil (2) Tidak terdapat perbedaan tindakan masyarakat yang pernah terkena konflik buaya-manusia di Kabupaten Aceh Singkil ditinjau berdasarkan jenis pendidikan, jenis kelamin dan suku.Kata Kunci: Tindakan, Konflik, Buaya Muara